Kerangka Konseptual Keamanan Layanan Sistem dalam Ekosistem Platform Digital Multilapis - Fadli Dalimunthe; Arif Maulana; Muhammad Partua Langka Situmeang; Muhammad Rasyya Alfarisi; Jakbar Ali Harahap (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid growth of digital services and API utilization in multi-layered platform ecosystems has expanded attack surfaces, increasing systemic security risks. Traditional security approaches focusing on individual components are insufficient to address cross-layer vulnerabilities, especially in cloud-native, microservices-based architectures. This study aims to develop a holistic conceptual framework for system service security in multi-layered digital platforms by identifying key layers, analyzing interdependencies, and mapping risks and controls across infrastructure, platform/middleware, applications, and governance layers. Using a qualitative literature review of publications since 2020, thematic and conceptual analyses were conducted to synthesize existing technical and governance practices. The proposed framework integrates defense-in-depth mechanisms, including network segmentation, API hardening, service mesh with mutual TLS, secure software development lifecycle, identity and access management, and governance policies, highlighting cross-layer dependencies and systemic risk propagation. Additionally, it addresses the trade-off between security and system performance, proposing adaptive and contextual strategies such as lightweight cryptography, selective protection, and orchestrated controls. The results suggest that security must be designed end-to-end, considering technical, operational, and governance dimensions, to ensure resilience, service availability, and user trust in complex digital platform ecosystems. This framework provides a theoretical and practical reference for designing robust, adaptive, and measurable security architectures.